(untitled) (Indian Journal of Animal Production and Management, 2014)
A survey was carried out to study reproductive parameters of swamp buffaloes of Manipur. Average age at first calving, gestation period, dry period, service period and inter calving period were found to be 5.02 ± 0.15 years, 324.63 ± 1.22, 291.30 ± 3.45, 180.90 ± 0.64 and 449.12 ± 4.38 days respectively. Statistical analysis revealed non-significant effect of types (Hill type and Plain type) of buffaloes on all these reproductive parameters.